Songs of blood and sword : a daughter's memoir - Bhutto, Fatima, 1982- (New York : Nation Books, 2010)
The author--whose father, Murtaza Bhutto, was murdered when she was just fourteen years old--tells the story of her political Pakistani family, from their roots as feudal landlords to their rise as political powerbrokers, as she tries to uncover the truth about her father's life and death.
Includes bibliographical references (p. 443-457) and index.
Keywords: Bhutto, Fatima, -- 1982- -- Family; Pakistan -- Biography; Pakistan -- History; Pakistan -- Politics and government